Eksperimen Pembelajaran Matematika Dengan Metode Number Heads Together (NHT) Dan Team Assisted Individualization (TAI) Terhadap Hasil Belajar Ditinjau Dari Motivasi Belajar Pada Siswa Kelas VII Semester Genap SMP Negeri 1 Kartasura Tahun 2015/2016 - Wikasari, Fabela Tri; , Idris Harta, M.A., Ph.D (2016)
This research is conducted to know: (1) the effect of learning method toward the understanding of learning outcomes of mathematics , (2) the effect of learning motivation to the understanding of learning outcomes of mathematics, (3) interaction between learning method and learning motivation to the understanding of learning outcomes of mathematics. The research is a quasi-experimental research. The population of the research is all of the 7th grades of SMP N 1 Kartasura in academic years of 2015/2016. There are two classes used as sampling is class VIIF and VIIH. The technique of sampling is cluster random sampling. The technique of collection data are test, questionnaire, and documentation. Technique of analyzing data used analysis of variance two different cells. The research result show that : (1) there is effect of learning method to understanding of learning outcomes of mathematics i.e. Fobs=4.326116699>Fα=4.01, (2) there is effect of learning motivation to understanding of learning outcomes mathematics i.e. Fobs=3.550426856>Fα=3.16, (3) there is no interaction between learning method and learning motivation to understanding of learning outcomes mathematics i.e. Fobs = 0.076247336 < Fα = 3.16.